The Influence of Ownership Structure on Leverage, Intellectual Capital Disclosure, and Firm Risk (A Study on Manufacturing Companies listed in Indonesia Stock Exchange, 2013-2018) - Asih Marini Wulandari; Sri Mangesti Rahayu; Nila Firdauzi Nuzula; Muhammad Saifi (Wacana Journal of Social and Humanity Studies, 2022)
This study aims to examine the influence of ownership structure on leverage, intellectual capital disclosure, and firm risk. It was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2013-2018 with a population of as many as 142 companies. The sample was selected using purposive sampling with a total sample of 21 companies. The analysis was done using SEM analysis with the WarpPLS approach. The results of the study show that ownership structure has a significant effect on leverage and intellectual capital disclosure but not to firm risk. Whereas, it is found that leverage significantly affects intellectual capital disclosure and firm risk. Intellectual capital disclosure is also proven to have a significant influence on firm risk. It can be said that the results of this study are useful for potential investors to estimate firm risk in making investment decisions. The results of the study are also important for a company management to manage firm risk.